bla(CTX-M) Genes in Escherichia coli Strains from Croatian Hospitals Are Located in New (bla(CTX-M-3a)) and Widely Spread (bla(CTX-M-3a) and bla(CTX-M-15)) Genetic Structures - Literacka, Elżbieta (American Society for Microbiology (ASM), 2009)
CTX-M-producing Escherichia coli isolates from three Croatian hospitals were analyzed. All bla(CTX-M-15) genes and one bla(CTX-M-3a) gene resided in widely spread ISEcp1 transposition modules, but other bla(CTX-M-3a) genes were in a new configuration with two IS26 copies, indicating a new event of gene mobilization from a Kluyvera ascorbata genome. The study confirmed the role of the E. coli ST131 clonal group with IncFII-type plasmids in the spread of bla(CTX-M-15) and of IncL/M pCTX-M3-type plasmids in the dissemination of bla(CTX-M-3a).